Distance Education during the COVID-19 pandemic - Fidalgo, Patricia (2021)
The COVID-19 pandemic led many Institutions of Higher Education (IHE) to transition to an online learning model. This change has increased the need to assess students' opinions about Distance Education (DE). This study surveyed students from Portugal, Ukraine and UAE about their views concerning DE during the pandemic. Almost one thousand students from the three countries responded and shared their opinions on DE and willingness to take online courses after the pandemic. Results show that although students may have a favourable opinion about DE, many would like to return to on-campus classes. Students also reported they would prefer to take blended and synchronous DE course formats after the pandemic.